A LITERATURE REVIEW: THE ROLE OF KSHARA IN AYURVEDA - Variya, *Hardik; Toshikhane, Hemant; H.S, Sathish; Jethava, Nilesh (AYUSHDHARA, 2017)
Ayurveda depends largely upon the medicinal plants for the therapy. Among the four Vedas - Rig-Veda, Yajurveda, Samaveda, and Atharvaveda - the Atharvaveda is considered to be one from which Ayurveda is derived and several medicinal plants are mentioned that can be used as a drugs. Kshara is the herbal extracts of plants, According to Sushruta, in Kshara Paka Vidhi Adhyaya has mentioned 23 drugs plants as: Mushkka, kutaj, Palash, Ashwakarna, Paribhadrak, Bhibitaka, Aragvadha, Tilwaka, Arka, Snuhi, Apamarga, Patla, Naktamal, Vrusha, Kadali, Chitraka, Putika, Asphota, Ashwamarak, Saptachanda, Agnimantha, Gunja, Koshataki from which Kshara can be prepared. Kshara can be a multiple combination of many herbs or may be from single herb. Kshara is useful in internal medicines in different formulation. i.e., Kshara Gutika (tablet), Vati, Ksharavleha, Kshara-Ghrita. Kshara is also useful in external application directly as Ksharapichu (gause-piece), Kshara Sutra, Ksharavarti. This alkaline preparation has many therapeutic usages and many surgical procedures. Ksharakarma is useful as the substitute of surgical instruments, because they can be used safely on the patients who are afraid of surgery. It has been proved to be effective in treating many disorders like Dushta Vrana (wounds), Bhagandara (Fistula-in-ano), Arsha (haemorrhoids), Charmakeela, Ashmari (Stone), Gulma Udara (ascites), Kushtha (leprosy), Rohini etc. External application of Kshara is indicated in children, weak persons and decrepit. Ksharakarma has been considered as a wealth and a strong weapon in Ayurvedic Pharmacopeia. In this paper we have described Preparation, classification, properties, Guna, Dosha, Indication, contra-indication, different formulae used in medicine, Matra, chemical composition and assessment.